The Implementation of Environmental Practices by Malaysian Contractors - Yahaya, Izyan (International Journal of Integrated Engineering, 2020)
Contractors, have huge role in ensuring little harm is inflicted on the environment and people as they are the one who directly involve in construction site activities. This paper focuses on the important contribution of contractor and their effort to minimize environmental impact through the implementation of Site Environmental Practices (SEPs). Site environmental practices are construction site activities that impose little harm to and have benefits on the environment. Through survey, it was revealed that SEPs implementation in Malaysia is still moderate. The contractors largely take a mere ‘occasional’ effort in addressing environmental matters. The apparent effort only can be seen on the issues related to air and water pollution controls. Moreover, efforts pertaining to prudent utilization of resource consumption in construction activities are seldom emphasized, let alone practiced. A slight disagreement on the level of SEPs between the two most influential managers, i.e. Top and Site Managers were also observed. These findings conclude that commitment of Malaysian contractors for SEPs still need to be improved.